The Distortion of Civilized Humanity and the Meaning of the Second Principle of Pancasila: A Theological Review and Its Implications for Indonesian Society - Ramly D. B. Lumintang (Scriptura Indonesia, 2026)
One of the major dangers within human civilization is the distortion of humanity, in which human beings become predators to one another (homo homini lupus). In essence, humans are social beings—noble creatures who are God-fearing and religious by nature—created to respect, honor, and love one another according to the intention of their Creator. Nevertheless, historical realities demonstrate that humans are also capable of extreme cruelty and violence toward their fellow beings. The history of the Indonesian nation records numerous humanitarian conflicts, including disputes and hostilities driven by ethnic, religious, racial, and intergroup tensions (SARA), which have persisted over time and left dark marks on the trajectory of Indonesian civilization. Such conditions should not occur, or at least can be minimized, through a shared national worldview and a firm commitment to the foundational principles of the state, particularly the second principle of Pancasila: Just and Civilized Humanity. This principle affirms that Indonesians are a civilized people who uphold mutual respect, dignity, and love for one another as fellow human beings. A truly civilized Indonesian society transcends barriers of race, ethnicity, and religion, thereby fostering a social life characterized by peace, tolerance, and harmony amid diversity.